Do Environmental Laws Matter for Corporate Ethics and Green Process Innovation in Environment Performance? The Moderating Role of Institutional Support - Khan, Huda; Amankwah-Amoah, Joseph; Laker, Benjamin; Lee, Richard; Sardana, Deepak (IEEE, 2025)
Drawing on institutional theory, this study disentangles the intricate relationships between environmental laws, corporate environmental ethics (CEE), green process innovation (GPI), and environmental performance. Using survey data from manufacturing firms in Pakistan, the study finds that environmental laws have a positive influence on GPI, and this association is mediated by CEE. Furthermore, the effects of environmental laws on environmental performance are sequentially mediated by CEE and GPI. In addition, institutional support plays a positive moderating role in enhancing the effects of environmental laws on CEE, as well as the effects of CEE on GPI. Theoretical, practical, and policy-related contributions are offered.
Keywords: Corporate ethics; environmental laws; environmental performance; green process innovation (GPI); institutional theory